Medborgardialog och delaktighet i Områdesprogram Lindängen : en studie av programmets policy för involvering av (invandrar-)boende i Lindängen - Farzin Saba, Nafiseh (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2016)
The purpose of this qualitative study is to find out to what extent Lindängens' immigrants with language difficulties has had participation and influence in Områdesprogram Lindängen planning decisions. In addition, what opportunities the program has offered them to encourage their participation, and what are the factors contributed in preventing the immigrants from participating and influencing the program. I conducted literature reviews and oral interviews with three civil servants, an architect, a politician and thirteen residents in the Lindängen in order to be able to answer the questions stated earlier in this study. The study has concluded that Områdesprogrammet Lindängen considered all local inhabitants as a whole, in other words, the area's immigrants with language difficulties are treated in the same way as the other residents through Framtidens hus, Allaktivitetshus, the area’s coordinator phone and email, newsletter Vår Lindängen and other means. In the middle of the program, there were opportunities given to the immigrants to learn Swedish or English at Allaktivitetshuset. In addition, Framtidens hus provided Arabic interpreter to Arabic immigrants. Evidently, factors that have prevented immigrants in the neighborhood from participating and influencing the program are language difficulties, lack of translated materials, lack of formal interpreters and lack of possibility for learning Swedish / English language (at the beginning of the program), the immigrants' mistrust of officials / government department and their lack of knowledge about difference between politicians and civil servants. Study has shown 50% of residents participating in civil dialogues which have happened especially at the beginning of the program, were immigrants. The following are the key lessons learned from the program experiences and future enhancements to urban planning for a more effective inclusion: - It is crucial to include all the residents’/immigrant’ experiences and views at the very beginning of the program rather than the later part. Thereby even the immigrants with language difficulties would still be able to contribute to the program at the planning stage of the program when the key decisions are made. - One approach for reaching out to immigrants is to reach out to their community leaders such as Imams in mosques, priests in churches and so on. To face immigrants with respect and their conditions can optimize their engagement and participation. - Offering multiple contact options to the (immigrant) residents can of course increase the possibility for them to contact and express their thoughts and ideas to responsible actors. - Finally, informing immigrant residents about the existing forms of participation and communication are as important as informing them about where and who they can turn to with questions, comments or complaints.